2017
DOI: 10.1002/14651858.cd011639.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance immunosuppression for adults undergoing liver transplantation: a network meta-analysis

Abstract: Based on low-quality evidence from a single small trial from direct comparison, tacrolimus plus sirolimus increases mortality and graft loss at maximal follow-up compared with tacrolimus. Based on very low-quality evidence from network meta-analysis, we found no evidence of difference between different immunosuppressive regimens. We found very low-quality evidence from network meta-analysis and low-quality evidence from direct comparison that cyclosporine A causes more retransplantation compared with tacrolimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 250 publications
2
35
0
Order By: Relevance
“…Analyzing Kaplan-Meier’s curves, it is possible to observe a higher graft survival rate on patients under tacrolimus-based therapeutic regimens when compared to those based on cyclosporine in the Full cohort. This finding is similar to that one of another cohort ( Jonas et al, 2005 ) and the finding of Rodriguez’s meta-analysis ( Rodríguez-Perálvarez et al, 2017 ). In multivariate analysis in the Full cohort, a higher proportion of azathioprine or mycophenolate use was related to a worse prognosis for the graft.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Analyzing Kaplan-Meier’s curves, it is possible to observe a higher graft survival rate on patients under tacrolimus-based therapeutic regimens when compared to those based on cyclosporine in the Full cohort. This finding is similar to that one of another cohort ( Jonas et al, 2005 ) and the finding of Rodriguez’s meta-analysis ( Rodríguez-Perálvarez et al, 2017 ). In multivariate analysis in the Full cohort, a higher proportion of azathioprine or mycophenolate use was related to a worse prognosis for the graft.…”
Section: Discussionsupporting
confidence: 90%
“…When these immunosuppressants are compared over longer periods, evidence shows no difference in patients’ survival. However, it is known that cyclosporine presents a higher rate of graft loss than tacrolimus ( Rodríguez-Perálvarez et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sirolimus (or rapamycin) entered the market first but the initial phase II randomized trial in liver transplantation had to be prematurely stopped because the experimental arm consisting of sirolimus plus tacrolimus resulted in an increased risk of graft loss and sepsis [107]. A subsequent network meta-analysis of randomized trials have demonstrated that sirolimus-based immunosuppression is associated with increased mortality rates as compared with other protocols and therefore there are concerns about using sirolimus as a first-line therapy in patients receiving a liver transplantation [108]. Everolimus has an improved safety profile as compared with sirolimus.…”
Section: Targeting Mtor Signaling In Hcc: From the Bench To The Clinicmentioning
confidence: 99%
“…Of calcineurin inhibitors, tacrolimus is preferred over cyclosporine for treating many types of autoimmune diseases and for preventing graft rejection after organ transplantation. This is largely owing to the fact that tacrolimus has consistently demonstrated better therapeutic effects and fewer adverse effects than cyclosporin in most comparative studies [ 58 62 ]. However, narrow therapeutic index and unpredictable bioavailability in humans (5%–67% with average of 27%) have made tacrolimus administration challenging for clinical practice [ 63 ].…”
Section: Promising Herb-drug Combinations For Rnsmentioning
confidence: 99%